2021
DOI: 10.1016/j.adro.2021.100757
|View full text |Cite
|
Sign up to set email alerts
|

A Beam-Specific Optimization Target Volume for Stereotactic Proton Pencil Beam Scanning Therapy for Locally Advanced Pancreatic Cancer

Abstract: We investigate two margin-based schemes for optimization target volumes (OTV), both isotropic expansion (2 mm) and beam-specific OTV, to account for uncertainties due to the setup errors and range uncertainties in pancreatic stereotactic pencil beam scanning (PBS) proton therapy. Also, as 2-mm being one of the extreme sizes of margin, we also study whether the plan quality of 2mm uniform expansion could be comparable to other plan schemes. Methods and Materials: We developed 2 schemes for OTV: (1) a uniform ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Range uncertainty margins, considering the heterogeneity of the beam path and often calculated as 3–5% of the water-equivalent beam path length, are routinely used in the clinic during proton planning [ 39 ]. Efforts have been put into reducing the planning margins and range uncertainties and further optimizing the dose to organs at the distal end of the target [ 40 ]. Studies have shown the application of dual-energy CT (DECT) to achieve a range uncertainty of 2% (versus 3.5%) for brain and prostate cancer patients [ 41 ].…”
Section: Dosimetric Datamentioning
confidence: 99%
“…Range uncertainty margins, considering the heterogeneity of the beam path and often calculated as 3–5% of the water-equivalent beam path length, are routinely used in the clinic during proton planning [ 39 ]. Efforts have been put into reducing the planning margins and range uncertainties and further optimizing the dose to organs at the distal end of the target [ 40 ]. Studies have shown the application of dual-energy CT (DECT) to achieve a range uncertainty of 2% (versus 3.5%) for brain and prostate cancer patients [ 41 ].…”
Section: Dosimetric Datamentioning
confidence: 99%
“…Our group has shown that injection of hydrogel spacer between the head of pancreas (HOP) and duodenum increases the duodenal sparing, and therefore, makes the dose escalation more feasible. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] However, the success of the spacer placement procedure is highly uncertain. Previous studies on rectal spacer have shown that hydrogel spacer injection is associated with risk of infection, inflammation, and softtissue wall infiltration.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 , 12 Recent studies have shown that hydrogel spacer resulted in a significant reduction of rectal dose during PT. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 However, the standard rectal hydrogel spacer is not visible on planning computed tomography (CT) and intraoperative cone‐beam CT that lack the adequate resolution and contrast to distinguish between the soft tissue (prostate and rectum) and hydrogel. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Thus, magnetic resonance imaging (MRI) is required to localize the hydrogel spacer, but anatomical changes, patient intolerance, MRI‐incompatible hardware, and the extra cost and time raise the need for an alternative spacer localization method.…”
Section: Introductionmentioning
confidence: 99%